2019
DOI: 10.1002/jcsm.12433
|View full text |Cite
|
Sign up to set email alerts
|

Myosteatosis is associated with poor physical fitness in patients undergoing hepatopancreatobiliary surgery

Abstract: Background Body composition assessment, measured using single‐slice computed tomography (CT) image at L3 level, and aerobic physical fitness, objectively measured using cardiopulmonary exercise testing (CPET), are each independently used for perioperative risk assessment. Sarcopenia (i.e. low skeletal muscle mass), myosteatosis [i.e. low skeletal muscle radiation attenuation (SM‐RA)], and impaired objectively measured aerobic fitness (reduced oxygen uptake) have been associated with poor post‐oper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
59
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(66 citation statements)
references
References 67 publications
7
59
0
Order By: Relevance
“…Second, the possibility of selection bias in patient inclusion in the study group must be considered, as abdominal CT scan is not a routine examination for COVID‐19 patients. Besides, physical activity levels were not analyzed in our study, although they have been widely associated with adipose tissue distribution in previous studies (16,28). The association between smoking and severity of COVID‐19 is controversial; it was not analyzed in our study because electronic medical records for smoking were not complete in our hospital during the outbreak period (37,38).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, the possibility of selection bias in patient inclusion in the study group must be considered, as abdominal CT scan is not a routine examination for COVID‐19 patients. Besides, physical activity levels were not analyzed in our study, although they have been widely associated with adipose tissue distribution in previous studies (16,28). The association between smoking and severity of COVID‐19 is controversial; it was not analyzed in our study because electronic medical records for smoking were not complete in our hospital during the outbreak period (37,38).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, lipids can be stored within skeletal muscle when the capacity for fat storage by subcutaneous and visceral tissue are exceeded, known as intramuscular fat (IMF) tissue (14). IMF deposition not only reflects the quality of muscle and poor physical function, it is also an independent risk factor for prognosis after cardiac and oncologic surgery (16‐19).…”
Section: Introductionmentioning
confidence: 99%
“…Body composition assessment, measured using routinely performed abdominal computed tomography (CT scan), demonstrated that both sarcopenia [61e63] and myosteatosis [64] contribute to poor postoperative outcomes following major abdominal surgery. As a recent study found that myosteatosis, and not sarcopenia, was associated with reduced aerobic fitness, combining preoperative body composition and aerobic fitness variables may provide additive risk assessment accuracy and guide interventions during the perioperative period in patients undergoing HPB surgery [65].…”
Section: Multidisciplinary Preoperative Risk Assessment In Older Patimentioning
confidence: 99%
“…Myosteatosis indicating fat deposition inside the muscles is defined as abnormal distribution of inter and intra-myocellular adipose tissue, which is related to reduced muscle quality, physical fitness and muscle function [ [19] , [20] , [21] ]. Computed tomography (CT) is one of common methods for accessing myosteatosis with a radiological marker termed skeletal muscle radiation attenuation (SM-RA) [ [21] , [22] , [23] ].…”
Section: Introductionmentioning
confidence: 99%